Pengaruh Perhatian Siswa Kompetensi Sosial Guru Dan Peran Orang Tua Terhadap Keaktifan Belajar Siswa Pada Masa Pandemi Covid-19 Di SMP Negeri 1 Sukasada - Widiari, Komang Ayu; Meitriana, Made Ary (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of student attention, teacher social competence, and the role of parents on student learning activity during the Covid-19 pandemic at SMP Negeri 1 Sukasada, both partially and simultaneously. This research is a type of causal research. The population is 250 students of class VIII SMPN1 Sukasada, and a sample of 154 respondents using the Yamane or Slovin formula and the proportional stratified random sampling technique. Data was collected through the distribution of questionnaires and observations, which were then analyzed using the t test and F test through the SPSS 28 for Windows program. The results showed that there was a partial and simultaneous influence of student attention, teacher social competence, and the role of parents on student learning activities during the Covid-19 pandemic at SMP Negeri 1 Sukasada.